Equoterapia no equilíbrio de indivíduos com esclerose múltipla: revisão sistemática - Lopes, Josiane (2021)
Introduction: Changes in the mechanisms of balance associated with multiple sclerosis (MS) have been the target of conservative interventions such as equine therapy. Thus, the objective of this systematic review was to analyze the evidence of the effectiveness of equine-assisted therapy in balance of individuals with MS. Methodology: This is a systematic review with searches in the databases Cinahl, Cochrane, Google Scholar, Lilacs, Lisa (ProQuest), PEDro, PsycINFO (APA), Pubmed and Scopus. Studies that described equine therapy protocols with or without comparison to conventional therapies that assessed variables of balance in individuals with MS were included. The studies were evaluated for methodological quality using the Physiotherapy Evidence Database Scale. Results: Among the 366 studies identified, seven studies were selected. Of these, the total sample was 138 individuals, most of them female, with an average diagnosis time of 9.36 ± 5.43 years. Only one study showed high methodological quality. All studies reported improvement or maintenance of parameters of balance. Concluding Remarks: Equineassisted therapy has a positive effect in improving the parameters of balance that also extrapolate to improve quality of life.